2022
DOI: 10.1093/ofid/ofac303
|View full text |Cite
|
Sign up to set email alerts
|

Different Clinical Presentations of Human Rhinovirus Species Infection in Children and Adults in Mexico

Abstract: Background Human Rhinoviruses (HRV) are a common cause of influenza-like illness, with the ability to infect the upper and lower respiratory tracts. In this study we aim to describe the clinical and molecular features of HRV infection in Mexican children and adults. Methods We performed a hospital-based, 4-year multicenter prospective observational cohort study of patients with influenza-like illness. Participants that tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…Multiple studies similar to ours have reported increasing positive detection rates of RV as RVA, RVC, and RVB ( Fig. 1A ) ( 9 , 39 , 40 ), the estimated effective population size was approximately consistent with it, but RVA did not produce a significant N e(t) advantage compared with RVC after 2000. In the future, further research is necessary to expand the scope of clinical RV detection, enabling the collection of a larger number of sequences.…”
Section: Discussionsupporting
confidence: 82%
“…Multiple studies similar to ours have reported increasing positive detection rates of RV as RVA, RVC, and RVB ( Fig. 1A ) ( 9 , 39 , 40 ), the estimated effective population size was approximately consistent with it, but RVA did not produce a significant N e(t) advantage compared with RVC after 2000. In the future, further research is necessary to expand the scope of clinical RV detection, enabling the collection of a larger number of sequences.…”
Section: Discussionsupporting
confidence: 82%